2018
DOI: 10.3389/fvets.2018.00154
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Mitigation of Risk of Waterborne Disease in Vietnam Among Small Scale Integrated Livestock Farmers

Abstract: The integrated livestock, crops, and fish (VAC) model of integrated small scale agriculture has been important to economic and ecological sustainability in Vietnam for many centuries. Recently, emerging waterborne diseases including avian influenza as well as the potential for zoonotic disease arising from small scale farms have jeopardized the VAC model. In order to promote mitigation of the risk of waterborne and other diseases in the VAC system, there needs to be recognition of the significant predictors of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…In response to the 2003-2006 HPAI outbreak and future threat of the disease, governments worldwide including Vietnam have prepared biosecurity protocols and policies to prevent the spread and possible outbreak of HPAI, with many guidelines specific to farmers. Although information on water protection as biosecurity protocol is generally lacking, farmers are advised to treat their water, use safe storage containers, and refrain from dumping waste in water sources (Hall & Le, 2018). The extent to which these recommendations are effective and actively practiced by smallholders in Vietnam has not been well researched, especially relating to water management and source protection (Conan, Goutard, Sorn, & Vong, 2012).…”
Section: Vietnam and Hpaimentioning
confidence: 99%
See 4 more Smart Citations
“…In response to the 2003-2006 HPAI outbreak and future threat of the disease, governments worldwide including Vietnam have prepared biosecurity protocols and policies to prevent the spread and possible outbreak of HPAI, with many guidelines specific to farmers. Although information on water protection as biosecurity protocol is generally lacking, farmers are advised to treat their water, use safe storage containers, and refrain from dumping waste in water sources (Hall & Le, 2018). The extent to which these recommendations are effective and actively practiced by smallholders in Vietnam has not been well researched, especially relating to water management and source protection (Conan, Goutard, Sorn, & Vong, 2012).…”
Section: Vietnam and Hpaimentioning
confidence: 99%
“…First, we anticipated that the numbers of farmers with HPAI cases was underreported in the sample. Past research has shown that less than 7% of VAC farmers would report a case of HPAI on their farm to public health or agricultural authorities (Hall & Le, 2018), often due to economic disincentives. Because HPAI is difficult to treat, the response to contain an outbreak by law is to cull the flock, which is damaging to the livelihood of VAC farmers who rely partially on poultry production (Hall & Le, 2018).…”
Section: Objective 3: Past Experience Factors Andmentioning
confidence: 99%
See 3 more Smart Citations